Quorum quenching and antibacterial activity of silver nanoparticles synthesized from Sargassum polyphyllum - Arunkumar, Mani; Suhashini, Karuppaiyan; Mahesh, Narayanan; Ravikumar, Raju (Bangladesh Journal of Pharmacology, 2014)
Development of efficient methodology for the green synthesis of silver nanoparticles using marine algae is a modern area of research in the field of phyconanotechnology. In this regard, the present study deals with green synthesis of silver nanoparticles (AgNPs) by using aqueous extracts of marine brown seaweed Sargassum polyphyllum. UV-visible spectral analysis reveals the formation of AgNPs by showing absorption maximum at 420 nm wavelength and SEM analysis clearly elucidate the polydispersed structure of AgNPs without aggregation and ranged in size from 37-43 nm. X-ray Diffraction pattern confirmed the AgNPs crystalline personality. The synthesized AgNPs showed more enduring antibacterial activity against test bacterial pathogens. Furthermore, the synthesized AgNPs exhibited varying level of inhibition of violacein production and swarming motility. In the near future, silver nanoparticles can be extremely useful in clinical medicine as an alternative method for the treatment of wound infection.